2006
DOI: 10.1016/j.bbrc.2006.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli thioredoxin homolog YbbN/Trxsc is a chaperone and a weak protein oxidoreductase

Abstract: Escherichia coli contains two thioredoxins, Trx1 and Trx2, and a thioredoxin-like protein, YbbN, which presents a strong homology in its N-terminal part with thioredoxin 1 and 2. YbbN, however, does not possess the canonical Cys-x-x-Cys active site of thioredoxins, but instead a Ser-x-x-Cys site. In addition to Cys-38, located in the SxxC site, it contains a second cysteine, Cys-63, close to Cys-38 in the 3D model. Cys-38 and Cys-63 undergo an oxidoreduction process, suggesting that YbbN functions with two red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…BSA, a nonchaperone control protein, does not offer any protection. Thioredoxin is well known for its thermoresistance (57) and in some cases has been described as a chaperone (58). The inactivation and aggregation of GAPDH in the presence of thioredoxin are still observed, although this protein slows down the process.…”
Section: Discussionmentioning
confidence: 99%
“…BSA, a nonchaperone control protein, does not offer any protection. Thioredoxin is well known for its thermoresistance (57) and in some cases has been described as a chaperone (58). The inactivation and aggregation of GAPDH in the presence of thioredoxin are still observed, although this protein slows down the process.…”
Section: Discussionmentioning
confidence: 99%
“…YbbN was initially reported to possess a weak thiol-disulfide protein oxidoreductase activity in an in vitro RNase A disulfide isomerization assay (10). However, the conserved thioredoxin CXXC active site motif necessary for this activity is mutated to a SXXC sequence in E. coli YbbN.…”
Section: Thioredoxin (Trx)mentioning
confidence: 99%
“…Caldas et al (10) found that YbbN alone is able to facilitate the refolding of urea-denatured citrate synthase (CS), ␣-glucosidase or ␤-clamp DnaN in vitro with an efficiency comparable to chaperones like DnaK and other heat shock proteins. However, a contradictory result was briefly * This work was supported, in whole or in part, by National Institutes of Health mentioned by Pan and Bardwell (5) using CS as a substrate.…”
Section: Thioredoxin (Trx)mentioning
confidence: 99%
See 1 more Smart Citation
“…coli (8), plants contain 2 large Trx families, namely the Trx and Trx-like proteins (9). Members of the Trx family have a distinct Trx motif, whereas the Trx-like protein family has a second functional domain in addition to the Trx motif (9).…”
mentioning
confidence: 99%